KONFLIK SOSIAL DALAM NOVEL THE MANGO SEASON KARYA AMULYA MALLADI - Dwi Lakshono (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2022)
This research’s title is sosial conflict in mango season novel by Amulya Malladi. In this novel, Priya is described as a girl that has lived in United State for seven years to study. After finished the study she have to come back to his country. Unwittingly, American lifestyle changed priya’s pointview to live. So, When she came back to India Priya conflict with his family because she has different pointview among his family to the live. The research’s purposes is to describe sosial conflict in mango season novel. This method’s research is descriptive’s qualitative according to moleong. The research’s subject is Amulya Malladi’s mango season. Sociology of literature is the approach of this research according to Damono to describe Priya’s conflict with his family. This research describe priya’s conflict with his family; Priya with his grandfather , Priya with his aunt, Priya with his grandmother, and Priya with his mom.